Risk analysis for severe traffic accidents in long road tunnels. (2016) - Gkoumas, Konstantinos; Santo, Carmine Di; Bontempi, Franco
In the recent years, with a globally increasing private motoring, tunnelling has gained a particular importance. After a series of dramatic accidents, the public opinion has turned its attention to tunnel fire safety. This paper focuses on the risk analysis in road tunnels, using the well-established Europe PIARC-OECD Quantitative Risk Assessment Model (QRAM). In the first part, a brief literature review - also on forensic investigations in tunnels - is performed, and the logic behind this method is briefly reassumed, focusing on the risk indicators. In the second part, a comprehensive risk analysis is performed in a long tunnel in Southern Italy, accounting for multifaceted aspects and parameters. The paper is completed with a sensitivity analysis on specific parameters that have an influence on the risk.